A.06 Selective amygdalohippocampectomy in pediatric medically refractory temporal lobe epilepsy yields worse seizure outcomes. (2nd June 2017) - Elliott, CA; Sinclair, D; Broad, A; Narvacan, K; Steve, T; Pugh, J; Snyder, T; Wheatley, B
Abstract : Background: Selective amygdalohippocampectomy (SAH) is a surgical option in well-selected cases of pediatric medically refractory temporal lobe epilepsy (TLE). The objective of this study was to compare the surgical outcome and the rate of reoperation for ongoing or recurrent seizures between SAH and anterior temporal lobectomy (ATL) in pediatric TLE.Methods: Retrospective review of 78 pediatric intractable TLE patients referred to the Comprehensive Epilepsy Program at our institution between 1988 and 2015 treated initially with either a trans-middle temporal gyrus SAH (19) or ATL (59). Patients underwent baseline long-term video electroencephalography and 1.5-Tesla MRI. Neuropsychological testing was performed preoperatively and 12-months postoperatively (including reoperations).Results: The mean follow-up was 64 months (range, 12-186 months). The average age at initial surgery was 10.6±5 years with an average delay of 5.7±4 years between seizure onset and surgery. Ultimately 78% were seizure-free (61/78) at most recent follow-up. Seizure freedom after initial surgical treatment was achieved in 81% of patients who underwent ATL (48 patients) versus 42% in SAH (8 patients; p<0.001). Of patients with ongoing disabling seizures following SAH, reoperation (ATL) was offered in 8 resulting in seizure freedom in 63%, without interval neuropsychological decline.Conclusions: SAH amongst well-selected pediatric TLE results in significantly worse seizure control compared with ATL.